The Effect of Artificial Repening Used The Calsium Carbida(CaC2) of Physical and Chemical Properties of Ambon Bananas (Musa paradisiaca var. sapientum (L.) Kunt)) - Anwar Sadat; Tamrin Tamrin; Cicih Sugianti (Universitas Sumatera Utara, 2015)
Banana is one of the best horticulture products in Indonesia. All this time, the ripening of banana has been done by the farmers. Artificial ripening was done using carbide with one kind of carbide concentration. The aim of this research was to determine the effect of carbide mass and ripening media on the physical and chemical quality of Ambon banana. The result showed that average of room air temperature between 28.48 °C, the average air temperature of the non vacuum media between 30.15 to 31.1°C, and the average air temperature of vacuum media ranged from 30.56 to 31.66 °C. The average of relative humidity from 74.76%, the average humidity of the non vacuum media between 78.68 to 79.45% and the vacuum media ranged from 79.02 to 80.24%. Respectively Water content of bananas in the non vacuum media ranged from 74.0 to 80.5% and the vacuum media ranged from 75.8 to 77.7%. Vitamin C levels of bananas with non vacuum media ranged from 99.7 to 108.5 mg per 100 g and vacuum media ranged from 17.6 to 32.3 mg per 100 g. The hardness of bananas in the non vacuum media ranged from 2.0 to 2.73 N and vacuum media ranged from 0.5 to 1.7 Newton. The soluble solid content of bananas in the non vacuum media ranged from 19.2 to 22.4 °brix and vacuum media ranged from 10.5 to 11.7 °brix. Keywords: bananas, artificial ripening, calcium carbide.